Association between prenatal or early postnatal exposure to perfluoroalkyl substances and language development in 18 to 36-month-old children from the Odense Child Cohort - Iben Have Beck; Niels Bilenberg; Helle Raun Andersen; Fabio Trecca; Dorthe Bleses; Tina Kold Jensen (BMC, 2023)
Abstract Background Perfluoroalkyl substances (PFAS) are persistent chemicals used in everyday consumer products leading to ubiquitous human exposure. Findings of impaired neurodevelopment after prenatal exposure to PFAS are contradictory and few studies have assessed the impact of postnatal PFAS exposure. Language development is a good early marker of neurodevelopment but only few studies have investigated this outcome separately. We therefore investigated the association between prenatal and early postnatal PFAS exposure and delayed language development in 18 to 36-month-old Danish children. Methods The Odense Child Cohort is a large prospective cohort. From 2010 to 2012 all newly pregnant women residing in the Municipality of Odense, Denmark was invited to participate. Concentration of perfluorooctane sulfonic acid (PFOS), perfluorooctanoic acid (PFOA), perfluorohexane sulfonic acid (PFHxS), perfluorononanoic acid (PFNA) and perfluorodecanoic acid (PFDA) were assessed in maternal serum collected in the 1st trimester of pregnancy and in child serum at 18 months. Parents responded to the Danish adaption of the MacArthur-Bates Communicative Development Inventories (MB-CDI) when their child was between 18 and 36 months. Language scores were converted into sex and age specific percentile scores and dichotomized to represent language scores above or below the 15th percentile. We applied Multiple Imputation by Chained Equation and conducted logistic regressions investigating the association between prenatal and early postnatal PFAS exposure and language development adjusting for maternal age, pre-pregnancy BMI, education and respectively fish intake in pregnancy or childhood and duration of breastfeeding in early postnatal PFAS exposure models. Results We found no significant associations between neither prenatal nor early postnatal PFAS exposure and language development among 999 mother-child pairs. Conclusion In this low-exposed cohort the finding of no association between early postnatal PFAS exposure and language development should be interpreted with caution as we were unable to separate the potential adverse effect of PFAS exposure from the well documented positive effect of breastfeeding on neurodevelopment. We, therefore, recommend assessment of child serum PFAS at an older age as development of the brain proceeds through childhood and even a small impact of PFAS on neurodevelopment would be of public health concern at population level due to the ubiquitous human exposure.